Clinical and Technical Challenges of Prosthesis–Patient Mismatch After Transcatheter Aortic Valve Implantation - Leone, Pier Pasquale; Fazzari, Fabio; Cannata, Francesco; Sanz-Sanchez, Jorge; Mangieri, Antonio; Monti, Lorenzo; Cozzi, Ottavia; Stefanini, Giulio Giuseppe; Bragato, Renato; Colombo, Antonio; Reimers, Bernhard; Regazzoli, Damiano (Frontiers in Cardiovascular Medicine, 2021)
Prosthesis–patient mismatch (PPM) is present when the effective area of a prosthetic valve inserted into a patient is inferior to that of a normal human valve; the hemodynamic consequence of a valve too small compared with the size of the patient's body is the generation of higher than expected transprosthetic gradients. Despite evidence of increased risk of short- and long-term mortality and of structural valve degeneration in patients with PPM after surgical aortic valve replacement, its clinical impact in patients subject to transcatheter aortic valve implantation (TAVI) is yet unclear. We aim to review and update on the definition and incidence of PPM after TAVI, and its prognostic implications in the overall population and in higher-risk subgroups, such as small aortic annuli or valve-in-valve procedures. Last, we will focus on the armamentarium available in order to reduce risk of PPM when planning a TAVI procedure.